Automated event extraction from email using pattern matching technique / Ahmad Tarmizi Razali - Razali, Ahmad Tarmizi (Faculty of Computer and Mathematical Sciences, 2007)
Email has become a popular communication media today. It's not only used for communication but also become an announcement media. One such example is annoimcements of different types of event. In many environments, seminar annoimcements, meeting announcements, workshop and etc., flood the inbox of users. A significant amount of tune is spent for each user to read the message, extract some important information from the announcement and then update their calendar. This process is time consuming and tedious. And because of that, users just leave important annoimcements in the inbox and then miss them. Therefore, the objective of this research is to develop an event extraction engine to make the process of jotting the information into calendar will be done automatically. The information extraction is done using the pattern matching (also known as knowledge engineering) approach.